Proceedings of the 26th ACM SIGSPATIAL International Conference on Advances in Geographic Information Systems 2018
DOI: 10.1145/3274895.3274940
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent geovisualizations for open government data (vision paper)

Abstract: Open government datasets (OGD) have been flooding the Web in recent years. Geovisualisations are the natural way of making sense of them, and have been gradually coming out. However, one key problem is the lack of flexibility of these visualizations, which severely limits their re-use in new scenarios. This article therefore proposes to increase the intelligence of existing geovisualisations by incorporating five features, to make better use of OGD: (i) automatic geographic data type recognition, (ii) generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…If we manage to realise map plasticity as envisioned in this paper, it may lay the foundation for a new understanding of what constitutes a map and enable much more flexible map-based systems. It could be a key enabler for intelligent geovisualisations [5], which is based on the vision of adapting maps to different input datasets while being capable of monitoring and maximising understanding on the user's side.…”
Section: Discussionmentioning
confidence: 99%

Map plasticity

Kray,
Degbelo
2019
Preprint
Self Cite
“…If we manage to realise map plasticity as envisioned in this paper, it may lay the foundation for a new understanding of what constitutes a map and enable much more flexible map-based systems. It could be a key enabler for intelligent geovisualisations [5], which is based on the vision of adapting maps to different input datasets while being capable of monitoring and maximising understanding on the user's side.…”
Section: Discussionmentioning
confidence: 99%

Map plasticity

Kray,
Degbelo
2019
Preprint
Self Cite
“…Contrasting our results with those from previous work may be useful here. In a study exploring geodata contribution on mobile devices via speech, Degbelo and Somaskantharajan (2020) reported that the speech modality was rated as usable, but not stimulating. This speaks against the argument that speech would be systematically rated by users as stimulating because it is used in a new application scenario.…”
Section: Key Takeawaysmentioning
confidence: 99%
“…start data exploration at zoom levels where others have highlighted interesting patterns first). This feature could contribute to advance the vision of better user activity support in intelligent geovisualizations (Degbelo and Kray, 2018).…”
Section: Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these datasets are georeferenced (and in the absence of reliable statistics, extrapolating results from previous work [22] suggests that at least 60% could be georeferenced). Within GIScience, re-use of these datasets has attracted the interest from research, and previous work has suggested, inter alia, semantic application programming interfaces to retrieve datasets according to their thematic categories [16], a platform to monitor open data re-use [14], a one-stop portal for open data search [23], and a vision of intelligent geovisualization to exploit these datasets [15]. Direct and indirect costs of open geospatial data provision were discussed in [29]; Benitez-Paez et al [5] presented an empirically-derived taxonomy of barriers to open data re-use from a user's standpoint; and Benitez-Paez et al [4] proposed a conceptual framework to improve the reusability of open geographic data in cities.…”
Section: Introductionmentioning
confidence: 99%